Agile and Lean: Management Strategy to Increase Efficiency and Responsibility - Radeswandri (Lembaga Anotero Scientific, 2024)
In an increasingly competitive business era, companies need to adapt quickly to market changes while maintaining operational efficiency. The Agile and Lean Management Approach has emerged as an effective strategy to achieve this goal, with Agile emphasizes the flexibility and responsiveness of customer needs, while Lean focuses on reducing waste and increasing value. This research uses a qualitative approach to explore the application of agile and lean strategies in the context of the organization. Data was collected through in -depth interviews, focus group discussions (FGD), and participatory observations in several companies that have implemented these two methodologies. Thematic analysis is used to identify the main patterns and themes of the data obtained. The results showed that the integration of agile and lean practices significantly improve operational performance and company responsiveness. Companies that apply these two approaches report improvements in customer satisfaction, process efficiency, and reduction of cycle time. In addition, the culture of sustainable improvement resulting from the application of these two methodologies contributes to the innovation and adaptability of the organization. To maximize the benefits of the application of Agile and Lean, companies are advised to provide adequate training to employees regarding the principles of the two approaches. Executive management support is also very important in creating an environment that supports change and innovation. With these steps, the organization can be better prepared to face challenges and take advantage of opportunities in the changing market